Transformation of Monohull to Catamaran Hybrid (Diesel-PV) Fishing Vessels to Reduce Exhaust Emissions - Rizky Irvana; Kamaruddin Abdullah; Erwin Susanto Sadirsan (International Journal of Marine Engineering Innovation and Research, 2022)
The fishermen's dependence on fossil fuels is still very high at 95.4% and has not decreased until now. The increased fuel price and reduced fossil fuel availability make fishermen struggle to fish. IMO (International Maritime Organization) noted that around 277 million tonnes of fuel are consumed by ships with fossil fuels. According to an emissions study conducted by IMO, 961 million tonnes of CO2 accounted for 2.5% of global emissions. This study aims to reduce exhaust emissions by vessels from fossil fuels by making the ship into a hybrid (Diesel-Pv). Making the ship a hybrid with solar panels will save fuel consumption. The method used is the trozzi method approach. The results obtained from changing the configuration to a hybrid can reduce the issued emission by around 57%.